Lean‐Based Redesign of Multidisciplinary Rounds on General Medicine Service. Issue 7 (2nd February 2018) - Kane, Marlena; Rohatgi, Nidhi; Heidenreich, Paul A.; Thakur, Akanksha; Winget, Marcy; Shum, Kenny; Hereford, James; Shieh, Lisa; Lew, Thomas; Hom, Jason; Chi, Jeffrey; Weinacker, Ann; et al.
Abstract : BACKGROUND: Multidisciplinary rounds (MDR) facilitate timely communication amongst the care team and with patients. We used Lean techniques to redesign MDR on the teaching general medicine service. OBJECTIVE: To examine if our Lean‐based new model of MDR was associated with change in the primary outcome of length of stay (LOS) and secondary outcomes of discharges before noon, documentation of estimated discharge date (EDD), and patient satisfaction. DESIGN, SETTING, AND PATIENTS: This is a pre‐post study. The preperiod (in which the old model of MDR was followed) comprised 4000 patients discharged between September 1, 2013, and October 22, 2014. The postperiod (in which the new model of MDR was followed) comprised 2085 patients between October 23, 2014, and April 30, 2015. INTERVENTION: Lean‐based redesign of MDR. MEASUREMENTS: LOS, discharges before noon, EDD, and patient satisfaction. RESULTS: There was no change in the mean LOS. Discharges before noon increased from 6.9% to 10.7% ( P < .001). Recording of EDD increased from 31.4% to 41.3% ( P < .001). There was no change in patient satisfaction. CONCLUSIONS: Lean‐based redesign of MDR was associated with an increase in discharges before noon and in recording of EDD.